2018
DOI: 10.1007/s00394-018-1881-0
|View full text |Cite
|
Sign up to set email alerts
|

24-Week β-alanine ingestion does not affect muscle taurine or clinical blood parameters in healthy males

Abstract: Purpose To investigate the effects of chronic beta-alanine (BA) supplementation on muscle taurine content, blood clinical markers and sensory side-effects. Methods Twenty-five healthy male participants (age 27 ± 4 years, height 1.75 ± 0.09 m, body mass 78.9 ± 11.7 kg) were supplemented with 6.4 g day −1 of sustained-release BA (N = 16; CarnoSyn™, NAI, USA) or placebo (PL; N = 9; maltodextrin) for 24 weeks. Resting muscle biopsies of the m. vastus lateralis were taken at 0, 12 and 24 weeks and analysed for taur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Another theoretical adverse effect of prolonged BA supplementation is a decrease in taurine content, given that the two share a transporter (Tau-T) (Shaffer and Kocsis, 1981). We have previously reported that very high BA doses (namely those commonly used in animal trials) result in a substantial depletion of intracellular taurine (Dolan et al, 2019b) but the same does not hold true for human studies (Dolan et al, 2019b;Saunders et al, 2020), likely due to the substantially lower doses typically employed (Dolan et al, 2019b). It is possible that the very high doses apparently required for MCarn saturation, may lead to taurine reductions, and so some caution must be taken in attempting to implement substantially higher doses than those currently in use.…”
Section: Discussionmentioning
confidence: 99%
“…Another theoretical adverse effect of prolonged BA supplementation is a decrease in taurine content, given that the two share a transporter (Tau-T) (Shaffer and Kocsis, 1981). We have previously reported that very high BA doses (namely those commonly used in animal trials) result in a substantial depletion of intracellular taurine (Dolan et al, 2019b) but the same does not hold true for human studies (Dolan et al, 2019b;Saunders et al, 2020), likely due to the substantially lower doses typically employed (Dolan et al, 2019b). It is possible that the very high doses apparently required for MCarn saturation, may lead to taurine reductions, and so some caution must be taken in attempting to implement substantially higher doses than those currently in use.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, alanine was chosen because it is the second most abundant circulating amino acid, is produced in muscle and metabolized in the liver as glutamine, and transports ammonia from the muscle to the liver to produce urea [17]. Furthermore, alanine did not significantly affect muscle metabolism or renal and hepatic function [35].…”
Section: Discussionmentioning
confidence: 99%
“…Beta-alanine is a non-proteogenic amino acid and the limiting factor for carnosine formation in the skeletal muscle (1). Chronic supplementation of BA between 4 and 24 weeks appears to be safe (14, 15) and can increase skeletal muscle carnosine content by up to 200% (16). Strong evidence supports the ergogenic role of BA supplementation for high-intensity exercise with meta-analytical data demonstrating its efficacy, particular during exercise 30 s to 10 min in duration (13).…”
Section: Introductionmentioning
confidence: 99%